Parametrisation of Coloured Petri Nets - Christensen, Søren; Mortensen, Kjeld Høyer (DAIMI Report Series, 1997)
In this paper we propose a conceptual framework for parametrisation of Coloured Petri Nets — a first step towards the formulation and formalisation of Parametric Coloured Petri Nets. We identify and characterise three useful kinds of parametrisation, namely value, type, and net structure parameters. While the two former kinds are simple to design the latter kind is more complex, and in this context we describe how net structure parametrisation naturally induces concepts like modules and scope rules. The framework is applied to a non-trivial example from the domain of flexible manufacturing. Finally we discuss implementation issues.